Efficient one-step synthesis of diarylacetic acids by electrochemical direct carboxylation of diarylmethanol compounds in DMSO - Senboku, Hisanori; Hayama, Mizuki (Beilstein Journal of Organic Chemistry, 2024)
An efficient one-step synthesis of diarylacetic acids was successfully performed by electrochemical direct carboxylation of diarylmethanol compounds in DMSO. Constant-current electrolysis of diarylmethanol species in DMSO using a one-compartment cell equipped with a Pt cathode and a Mg anode in the presence of carbon dioxide induced reductive C(sp3)−O bond cleavage at the benzylic position in diarylmethanol compounds and subsequent fixation of carbon dioxide to produce diarylacetic acids in good yield. This protocol provides a novel and simple approach to diarylacetic acids from diarylmethanol species and carbon dioxide without transformation of the hydroxy group into appropriate leaving groups, such as halides and esters including carbonates.
Keywords: C(sp3)–O bond cleavage; diarylacetic acid; diarylmethanol; electrochemical reduction; fixation of carbon dioxide